2019
DOI: 10.1038/s41390-019-0582-6
|View full text |Cite
|
Sign up to set email alerts
|

A perfect storm: fetal inflammation and the developing immune system

Abstract: Histologic chorioamnionitis is an inflammatory disorder of the placenta that commonly precedes preterm delivery. Preterm birth related to chorioamnionitis and fetal inflammation has been associated with a risk for serious inflammatory complications in infancy. In addition, preterm infants exposed to chorioamnionitis may be more susceptible to infection in the neonatal intensive care unit and possibly later in life. A significant body of work has established an association between chorioamnionitis and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 170 publications
3
16
0
1
Order By: Relevance
“…First, activation of the fetal inflammatory response is an independent predictor of neonatal morbidity after adjustment for gestational age and obstetric indication for delivery (20). Second, sequencing studies have shown that exposure to HCA results in fetal immune programming in preterm infants with modulation of monocyte responses (58)(59)(60). Third, intra-amniotic inflammation is associated with adverse perinatal outcomes whether or not microbes are detected (61).…”
Section: Discussionmentioning
confidence: 99%
“…First, activation of the fetal inflammatory response is an independent predictor of neonatal morbidity after adjustment for gestational age and obstetric indication for delivery (20). Second, sequencing studies have shown that exposure to HCA results in fetal immune programming in preterm infants with modulation of monocyte responses (58)(59)(60). Third, intra-amniotic inflammation is associated with adverse perinatal outcomes whether or not microbes are detected (61).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal inflammatory response syndrome (FIRS) is defined by increased systemic inflammatory cytokine concentrations, funisitis, and fetal vasculitis. Multiorgan involvement in FIRS has been demonstrated in the hematopoietic system, thymus, adrenal glands, skin, kidneys, heart, lung, and brain [3]. Biological markers including C-reactive protein, procalcitonin and interleukin-6 levels in cord blood can be used to attempt to identify fetal inflammation, but their specificity is limited [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The fetal inflammatory response 7 is an area of intense recent interest, as it is associated with multiple negative postnatal outcomes, including altered immune function. 8 Whether these are mediated in part by changes in iron metabolism remains speculative.…”
mentioning
confidence: 99%